Environmental context alters plant–soil feedback effects on plant coexistence - Jeremy A. Collings; Lauren G. Shoemaker; Jeffrey M. Diez (Ecology, 2025)
Plant–soil feedbacks are thought to mediate outcomes of plant competition through microbially driven positive or negative feedback loops. Plant–microbe interactions are known to depend on the underlying environmental context, yet most efforts to understand how plant–soil feedbacks mediate species coexistence have not considered these context dependencies. Here, we use modern coexistence theory to assess how this environmental context‐dependence of plant–microbe interactions might influence plant coexistence, and through which species interactions environmental context‐dependencies are most likely to modify coexistence outcomes. First, we found that the component species interactions in a plant–soil feedback model vary in their relative effects, with microbes impacting fitness ratios more so than direct plant–plant interactions. We also found that linear effects of the environment on plant–soil feedbacks result in nonlinear changes in niche differences and fitness ratios, which can result in altered predictions for coexistence, shifting species pairs from regions of coexistence to competitive exclusion or even priority effects. Finally, we extended our model to simulate how environmental dependence of plant–soil feedbacks in a well‐studied invasive species, garlic mustard ( Alliaria petiolata ), may help explain invasion dynamics across environmental regions. We also discuss paths forward in empirically parameterizing context‐dependent coexistence models using greenhouse experiments. This work builds on recent efforts to integrate plant–soil feedback theory with modern coexistence theory, suggesting that context‐dependencies of plant–microbe interactions may more strongly alter fitness ratios compared to plant–plant interactions. Our results highlight how context‐dependent plant–soil feedbacks may help explain spatial and temporal variation in plant community dynamics and suggest that the underlying mechanism of these dynamics depends on the relative sensitivity of particular species interactions to the environmental gradient.

Assessing wood grain and twist in a 2-year-old Eucalyptus bosistoana breeding population - Monika Sharma; Stephanie M. Dijkstra; Ashley Garrill; David A. Collings; Clemens M. Altaner (Trees, 2024)
Key message Radial grain patterns in young E. bosistoana trees are not random but are under genetic control and are correlated to other properties. Detailed high-resolution grain assessments match results from economical larger resolution techniques. Abstract Interlocked grain affects stem properties and timber value. Eucalyptus bosistoana is an emerging plantation species that is supported by a breeding programme, and which shows prominent interlocked grain. Grain assessments are difficult, either restricted in their spatial resolution or resource demanding. Comparative analysis of flexible and high-resolution X-ray microtomography grain measurements were shown to match the economical splitting test. Splitting demonstrated that, on average, grain in the 2-year-old E. bosistoana trees was straight close to the pith becoming slightly left-handed over the first 4 mm, but then developing a strong right-handed twist reaching an average of almost 5° by 12 mm. There was, however, a large degree of variability. Further, grain measures obtained from splitting tests correlated to the observed twisting of the stems. Lastly, twisting of timber was under genetic control. The combination of a heritability ( h 2 ) value of 0.34 and a coefficient of genetic variation value (r g ) of 44% means that our assessment techniques for young trees could be incorporated into a breeding programme.

Partitioning the sources of sediment organic carbon in South African seagrass meadows - A Bossert; S von der Heyden; J Colling; A Ndhlovu (African Journal of Marine Science, 2024)

Characterisation of the trans-membrane nucleoporins GP210 and NDC1 in Arabidopsis thaliana - Patrick P. Collins; Ronan C. Broad; Krithika Yogeeswaran; Arvind Varsani; Anthony M. Poole; David A. Collings (Plant Science, 2023)

Determination of trace elements in Sergio mirim: an evaluation of sample preparation methods and detection techniques - Jaime S. Mandlate; Bruno M. Soares; Carlos F. F. Andrade; Leonir A. Colling; Ednei G. Primel; Marcia F. Mesko; Fabio A. Duarte (Environmental Science and Pollution Research, 2020)

To pool or not to pool? Guidelines for pooling samples for use in surveillance testing of infectious diseases in aquatic animals - Emilie Laurin; Krishna Thakur; Peter G. Mohr; Paul Hick; Mark St. J. Crane; Ian A. Gardner; Nicholas J. G. Moody; Axel Colling; Ingo Ernst (Journal of Fish Diseases, 2019)
Samples from multiple animals may be pooled and tested to reduce costs of surveillance for infectious agents in aquatic animal populations. The primary advantage of pooling is increased population‐level coverage when prevalence is low (

Compressibility and structure behaviour of maruyamaite (K-tourmaline) from the Kokchetav massif at high pressure up to 20 GPa - Anna Yu. Likhacheva; S. V. Rashchenko; Kira A. Musiyachenko; Andrey V. Korsakov; Ines E. Collings; Michael Hanfland (Mineralogy and Petrology, 2019)

Quantifying the discriminatory power of remote sensing technologies for benthic habitat mapping - Simon Collings; Norm A. Campbell; John K. Keesing (International Journal of Remote Sensing, 2019)

Allochthonous versus autochthonous organic matter sustaining macroconsumers in a subtropical sandy beach revealed by stable isotopes - A. M. Garcia; M. C. L. M. Oliveira; C. Odebrecht; J. L. A. Colling; J. P. Vieira; F. L. Rodrigues; R. F. Bastos (Marine Biology Research, 2019)

Ferric Sulphate Coagulant Obtained by Leaching from Coal Tailings - J. C. C. C. Menezes; A. V. Colling; R. A. S. Silva; Rafael Hoppen Dos Santos; I. A. H. Scheneider (Mine Water and the Environment, 2017)

Induction of anthocyanin in the inner epidermis of red onion leaves by environmental stimuli and transient expression of transcription factors - Elizabeth J. Wiltshire; Colin C. Eady; David A. Collings (Plant Cell Reports, 2017)

Comparative analysis of common regions found in babuviruses and alphasatellite molecules - Daisy Stainton; Darren P. Martin; David A. Collings; Arvind Varsani (Archives of Virology, 2017)

A temperature-sensitive allele of a putative mRNA splicing helicase down-regulates many cell wall genes and causes radial swelling in Arabidopsis thaliana - Paul A. Howles; Leigh K. Gebbie; David A. Collings; Arvind Varsani; Ronan C. Broad; Stephen Ohms; Rosemary J. Birch; Ann H. Cork; Tony Arioli; Richard E. Williamson (Plant Molecular Biology, 2016)

Identification and in silico characterisation of defective molecules associated with isolates of banana bunchy top virus - Daisy Stainton; Darren P. Martin; David A. Collings; John E. Thomas; Arvind Varsani (Archives of Virology, 2016)

The life of phi: the development of phi thickenings in roots of the orchids of the genus Miltoniopsis - Nurul A. Idris; David A. Collings (Planta, 2015)

EURRECA—Estimating Zinc Requirements for Deriving Dietary Reference Values - Nicola M. Lowe; Fiona C. Dykes; Anna-Louise Skinner; Sujata Patel; Marisol Warthon-Medina; Tamás Decsi; Katalin Fekete; Olga W. Souverein; Carla Dullemeijer; Adriënne E. Cavelaars; Lluis Serra-Majem; Mariela Nissensohn; et al. (Critical Reviews in Food Science and Nutrition, 2013)

EURRECA—Evidence-Based Methodology for Deriving Micronutrient Recommendations - Rosalie A. M. Dhonukshe-Rutten; Jildau Bouwman; Kerry A. Brown; Adriënne E. J. M. Cavelaars; Rachel Collings; Evangelia Grammatikaki; Lisette CPGM de Groot; Mirjana Gurinovic; Linda J. Harvey; Maria Hermoso; Rachel Hurst; Bas Kremer; et al. (Critical Reviews in Food Science and Nutrition, 2013)

The association of peroxisomes with the developing cell plate in dividing onion root cells depends on actin microfilaments and myosin - David A. Collings; John D. I. Harper; Kevin C. Vaughn (Planta, 2003)

The distributional changes and role of microtubules in Nod factor-challenged Medicago sativa root hairs - Ravisha R. Weerasinghe; David A. Collings; Eva Johannes; Nina Strmgren Allen (Planta, 2003)

Rapid serological profiling by enzyme-linked immunosorbent assay and its use as an epidemiological indicator of foot-and-mouth disease viral activity - I. E. Bergmann; E. Neitzert; V. Malirat; S. Ortiz; A. Colling; C. Snchez; E. Correa Melo (Archives of Virology, 2003)

Response of freshwater microcosm communities to nutrients, fish, and elevated temperature during winter and summer - D. McKee; D. Atkinson; S. E. Collings; J. W. Eaton; A. B. Gill; I. Harvey; K. Hatton; T. Heyes; D. Wilson; B. Moss (Limnology and Oceanography, 2003)
Under conditions of stress, shallow freshwater ecosystems can undergo a state change characterized by the rapid loss of macrophytes and subsequent dominance of phytoplankton. Elevated water temperature may promote such change. Here we report the impact of two warming regimes (continuous 3°C above ambient and 3°C above ambient during summer only), with two nutrient loadings and the presence or absence of fish, on 48 microcosm ecosystems created to mimic shallow pond environments. We found that warming did not significantly encourage phytoplankton blooms, even in combination with increased nutrients and fish. Instead, macrophyte communities remained dominant. Macrophyte‐associated invertebrates (gastropods and ostracods) increased in numbers in the warmed microcosms, potentially helping to stabilize the macrophyte communities. Nevertheless, warming produced trends in water chemistry that could be problematic. It increased phosphorus concentrations, total alkalinity, and conductivity. It decreased pH and oxygen saturation and increased the frequency of severe deoxygenation. These trends were largely independent of the other experimental treatments and support the suggestion that moderate warming has the potential to exacerbate existing eutrophication problems.

Demonstration of prominent actin filaments in the root columella - David A. Collings; Gabor Zsuppan; Nina S. Allen; Elison B. Blancaflor (Planta, 2001)

Microtubule and actin filament organization during acentral divisions in potato suspension culture cells - David A. Collings; Anne Mie C. Emons (Protoplasma, 1999)

Growth dynamics and cytoskeleton organization during stem maturation and gravity-induced stem bending in Zea mays L. - David A. Collings; Heike Winter; Sarah E. Wyatt; Nina S. Allen (Planta, 1998)